A VHH-Fc Fusion Targeted to the Chloroplast Thylakoid Lumen Assembles and Neutralizes Enterohemorrhagic E. coli O157:H7 - Chin-Fatt, Adam; Menassa, Rima (Frontiers in Plant Science, 2021)
Chimeric fusion proteins comprising a single domain antibody (VHH) fused to a crystallizable fragment (Fc) of an immunoglobulin are modular glycoproteins that are becoming increasingly in demand because of their value as diagnostics, research reagents and passive immunization therapeutics. Because ER-associated degradation and misfolding may potentially be limiting factors in the oxidative folding of VHH-Fc fusion proteins in the ER, we sought to explore oxidative folding in an alternative sub-compartment, the chloroplast thylakoid lumen, and determine its viability in a molecular farming context. We developed a set of in-house expression vectors for transient transformation of Nicotiana benthamiana leaves that target a VHH-Fc to the thylakoid lumen via either Sec or Tat import pathways. Compared to stromal (6.63±3.41 mg/kg fresh weight (FW), cytoplasmic (undetectable) and Tat-import pathways (5.43±2.41 mg/kg FW), the Sec-targeted VHH-Fc showed superior accumulation (30.56±5.19 mg/kg FW), but was less than that of the ER (51.16±9.11 mg/kg FW). Additionally, the introduction of a rationally designed de novo disulfide bond enhances in planta accumulation when introduced into the Sec-targeted Fc fusion protein from 50.24±4.08 mg/kg FW to 110.90±6.46 mg/kg FW. In vitro immunofluorescent labelling assays on VHH-Fc purified from Sec, Tat, and stromal pathways demonstrate that the antibody still retains VHH functionality in binding E. coli O157:H7 and neutralizing its intimate adherence to human epithelial type 2 cells. These results overall provide a proof of concept that the oxidative folding environment of the thylakoid lumen may be a viable compartment for stably folding disulfide-containing recombinant VHH-Fc proteins.